Cash Demand Sensitivity: Post-Tax Amnesty Shadow Economy Estimation in Indonesia - Pidah Febriyanti; Herman Sambodo (Economics Development Analysis Journal, 2024)
Indonesia has consistently failed to meet its tax revenue targets in recent years, primarily due to extensive shadow economy activities aimed at tax evasion. This study seeks to measure the sensitivity of cash demand in estimating the shadow economy across Indonesia's 34 provinces during the post-tax amnesty period from 2016 to 2022 and to assess its impact on potential tax revenue losses. Utilizing a quantitative methodology, the research employs panel data regression with a Random Effects Model. The shadow economy is estimated using a monetary approach model based on cash demand sensitivity. The dependent variables include total currency demand and potential tax revenue, while the independent variables comprise tax burden, inflation rate, Gross Regional Domestic Product (GRDP), financial and technological innovation (represented by internet use for financial purposes), and the shadow economy. The findings reveal that the tax burden, inflation, and financial/technological innovations do not significantly influence cash demand, whereas income has a significant positive effect. Moreover, the shadow economy substantially affects potential tax revenue losses. On average, the shadow economy across the 34 provinces amounts to IDR 292.152 billion, with an average potential tax revenue loss of IDR 35.306 billion